SINGLE-BLIND, RANDOMIZED, CONTROL TRIAL OF A UNANI COMPOUND FORMULATION IN ILTEHAB TAJAWEEFE ANAF MUZMIN - ZAIDI, ZEHRA; KHAN, ASIM ALI; JABEEN, AZHAR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to establish the efficacy and tolerability of oral Unani formulations with inhalation of Kalonji and to provide safe, effective, and economical treatment for Iltehab Tajaweefe Anaf Muzmin (chronic rhinosinusitis [CRS]). Methods: A randomized single-blind, comparative study of 40 patients of CRS. The patients were randomly allocated to two groups each consisting of 20 patients. In Group A, oral Unani formulation of Katan (Linum usitatissimum), Filfil Siyah (Piper nigrum), and honey was given 6 g BD with steam inhalation of Kalonji (Nigella sativa) and Tab Alaspan 1 BD with Karvol Plus inhalation was given in Group B. Results: Statistical analysis of the data was done using paired t test by comparing the visual analog scale score of all major and minor symptoms before and after treatment. The result is statistically highly significant in Group A (p<0.0001) and it is significant in Group B. (p<0.01). Conclusion: It may be concluded that the oral Unani formulation with inhalation of Kalonji has statistically highly significant effect on major and minor symptoms of CRS. A multicentric trial of the test drug on larger sample size for a longer duration is required to establish the efficacy of the formulation on CRS.